2004
DOI: 10.1590/s0100-879x2004000400018
|View full text |Cite
|
Sign up to set email alerts
|

Hypotrophy of conduit artery walls of the offspring of nitric oxide-defective rats

Abstract: The objective of the present study was to investigate the structure of the arterial walls of the offspring stemming from nitric oxide (NO)-defective hypertensive parents. The parents were treated with N Gnitro-L-arginine methyl ester (40 mg kg -1 day -1 ) for 5 weeks. Blood pressure was measured noninvasively in six 30-day-old rats and nine age-matched controls. The cardiovascular system was perfused with glutaraldehyde at 120 mmHg. The thoracic aorta and carotid artery were processed for electron microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Griffin et al (1991) reported that infusion of subpressor doses of ang II leads to an increase in the thickness of the arterial media and ratio of media to lumen in the resistant arteries. Further, the discrepancy between BP and trophicity of the arterial wall has also been observed in 4-week-old Wistar rats that were progenies of NO-deficient parents, where hypertension was accompanied with hypotrophy of the heart and arterial wall (Kristek and Gerova 2004). In addition, BPindependent decrease in cardiac hypertrophy was observed after long-term administration of exogenous NO donors and/or sildenafil to SHRs (Kristek et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Griffin et al (1991) reported that infusion of subpressor doses of ang II leads to an increase in the thickness of the arterial media and ratio of media to lumen in the resistant arteries. Further, the discrepancy between BP and trophicity of the arterial wall has also been observed in 4-week-old Wistar rats that were progenies of NO-deficient parents, where hypertension was accompanied with hypotrophy of the heart and arterial wall (Kristek and Gerova 2004). In addition, BPindependent decrease in cardiac hypertrophy was observed after long-term administration of exogenous NO donors and/or sildenafil to SHRs (Kristek et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Similar lower BW was observed in 4week-old rats from dams, which were administrated with L-NAME (Gerova et al 2002). Long-term administration of L-NAME evokes hypertension in offspring and adults (Kristek and Gerova 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the high variability of transcript measurements in the individual hearts of db/db mice questions the significance of this finding and hampers the conclusion drawn on the dynamics of ANP expression during the progression of cardiac pathology in this model. Alteration in the cardiovascular system, such as atrophy of the arterial walls in the offspring of NO‐defective rats, has been shown (Kristek & Gerova, 2004), suggesting the contribution of NO deficiency in cardiac atrophy. This is in agreement with the lower expression of NOS in db/db mice and indicates that endothelial dysfunction is involved in cardiovascular complications of diabetes (Forstermann & Munzel, 2006).…”
Section: Discussionmentioning
confidence: 99%